Establishment of a cohort for deep phenotyping of the immune response to influenza vaccination among elderly individuals recruited from the general population. Issue 7 (3rd July 2017) - Akmatov, Manas K.; Riese, Peggy; May, Marcus; Jentsch, Leonhard; Ahmed, Malik W.; Werner, Damaris; Rösel, Anja; Tyler, Megan; Pessler, Kevin; Prokein, Jana; Bernemann, Inga; Klopp, Norman; et al.
ABSTRACT: Elderly individuals have the highest burden of disease from influenza infection but also the lowest immune response to influenza vaccination. A better understanding of the host response to influenza vaccination in the elderly is therefore urgently needed. We conducted a biphasic prospective, population-based study from Dec. 2014 to May 2015 (pilot study) and Sept. 2015 to May 2016 (main study). Individuals 65–80 y of age were randomly selected from the residents' registration office in Hannover, Germany, for the pilot (n = 34) and main study (n = 200). The pilot study tested recruitment for study arms featuring 2, 4, or 5 visits/blood draws. The 5-visit (day 0, 1/3, 7, 21, 70 with respect to vaccination) study arm was selected for the main study. Both studies featured vaccination with Fluad™ (Novartis, Italy), a detailed medical history, a physical exam, recording of adverse events, completion of a questionnaire on common infections and an end-of-study questionnaire, and blood samples. Response rates in the pilot and main studies were 3.7% and 4.0%, respectively. Willingness to participate did not differ among the study arms (Fisher's exact test, p = 0.44). In both studies, there were no losses to follow-up. Compliance with study visits, blood sampling and completion of the questionnaires was very high (100%, >97%, 100%, respectively), as were participants' acceptance of and satisfaction with both phases of the study. The low response rates indicate the need for optimized recruitment strategies if the study population is to be representative of the general population. Nonetheless, the complex prospective study design proved to be highly feasible.